2008
DOI: 10.1089/cpb.2007.9935
|View full text |Cite
|
Sign up to set email alerts
|

Depth Perception in Virtual Reality: Distance Estimations in Peri- and Extrapersonal Space

Abstract: The present study investigated depth perception in virtual environments. Twenty-three participants verbally estimated ten distances between 40 cm and 500 cm in three different virtual environments in two conditions: (1) only one target was presented or (2) ten targets were presented at the same time. Additionally, the presence of a metric aid was varied. A questionnaire assessed subjective ratings about physical complaints (e.g., headache), the experience in the virtual world (e.g., presence), and the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
111
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(121 citation statements)
references
References 4 publications
9
111
1
Order By: Relevance
“…Accuracy will be higher when targets are displayed closer to the observer. This is with the assumption that egocentric and exocentric distance affect each other and in majority of the studies, in physical and virtual reality, accuracy was higher in near field visual space [28].…”
Section: Hypothesesmentioning
confidence: 55%
See 1 more Smart Citation
“…Accuracy will be higher when targets are displayed closer to the observer. This is with the assumption that egocentric and exocentric distance affect each other and in majority of the studies, in physical and virtual reality, accuracy was higher in near field visual space [28].…”
Section: Hypothesesmentioning
confidence: 55%
“…Each participant made 48 (4 Â 3 Â 4) trials of which, based on the classified values, on average, 36 (SD = 9.03) underestimations, 9.2 (SD = 6.41) accurate and 2.8 (SD = 3.05) overestimations were observed. The judgment was considered accurate if the signed error is between À0.01 and +0.01, because, even in real world some small error was evident [28]. It can generally be observed that exocentric distance was underestimated in all tested conditions where the accuracy of judgment was only 83.6% (SD = 0.145).…”
Section: Resultsmentioning
confidence: 97%
“…Similarly, movements were slower in both groups of subjects when reaching in a 3D VE viewed through an HMD compared to an equivalent PE [11]. Movement parameters can be influenced by object-based visual cues [25] and the size and quality of the viewing environment [26]. Slowing of movement may have been due to viewing the VE through the HMD which reportedly decreases depth perception for distant objects [27].…”
Section: A Effect Of the Environment On Reaching And Graspingmentioning
confidence: 88%
“…In RE, the processing unit can quickly select the optimal response way based on practical experience. However, it is more difficult to accurately estimate the position of a virtual object in low-fidelity VE (Arthur et al, 1997;Witmer and Kline, 1998;Keyson, 2000;Armbrüster et al, 2008). Without practical experience, the cognitive cycle from the visual module to the processing unit to the manual module must be repeated many times (trials) while subjects are performing their tasks.…”
Section: Discussionmentioning
confidence: 99%